Is the association between FDI and inflation symmetric or asymmetric? Evidence from ARDL and NARDL techniques - Hossain, Saddam; Hosen, Mosharrof; Mohd Thas Thaker, Hassanudin; Sharma, Gagan Deep; Masih, Mansur; Khee Pek, Chuen (World Scientific Publishing Company, 2023)
Based on the demand-pull and cost-push theory, this study examines the relationship between foreign direct investment (FDI) and inflation nexus by using time series technique of Autoregressive Distributed Lags (ARDL). Asymmetry assumption was investigated by employing relatively advanced Nonlinear Autoregressive Distributed Lag (NARDL) method. Annual data from 1973 to 2017 has been collected from the World Bank database and DataStream. The results revealed that Bangladesh’s FDI inflow has a significant impact on the inflation rate, which augurs well for the economy. In addition, we also discover an asymmetric relationship in the long run and symmetric relationship in the short run. Several policy recommendations of these findings are provided.